Mindfulness-Based Intervention and Sexuality: A Systematic Review - Ciaurriz Larraz, Amaia Miren; Villena, Alejandro; Mestre-Bach, Gemma; Chiclana Actis, Carlos (International Journal of Sexual Health, 2022)
Mindfulness is defined as “the ability to pay attention in a particular way, in the present moment to the body and mind, with purpose and without judgment.” From a scientific perspective, mindfulness has been described as a mental function that allows us to keep the focus of our attention on an immediate experience of the present. Sexual dysfunctions are characterized by a clinically significant disturbance in a person’s ability to respond sexually or to experience sexual pleasure. Therefore, mindfulness may be an effective way of re-routing one’s focus away from negative memories or anticipated sexual problems and onto the sensations that are unfolding at the moment.
Keywords: mindfulness; sexuality; JCR